2021
DOI: 10.1109/tnsre.2021.3105669
|View full text |Cite
|
Sign up to set email alerts
|

Classification of First-Episode Schizophrenia, Chronic Schizophrenia and Healthy Control Based on Brain Network of Mismatch Negativity by Graph Neural Network

Abstract: Mismatch negativity (MMN) has been consistently found deficit in schizophrenia, which was considered as a promising biomarker for assessing the impairments in preattentive auditory processing. However, the functional connectivity between brain regions based on MMN is not clear. This study provides an in-depth investigation in brain functional connectivity during MMN process among patients with firstepisode schizophrenia (FESZ), chronic schizophrenia (CSZ) and healthy control (HC). Electroencephalography (EEG) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
23
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 73 publications
1
23
0
2
Order By: Relevance
“…For example, Chang et al found that, compared to support vector machine (SVM), a GNN model of electroencephalography-based brain networks showed better performance in distinguishing among first-episode, chronic schizophrenia patients and controls. 28 Likewise, by using GNN combined with functional connectome data, Oh et al achieved a classification accuracy of 83.13%, which outperformed alternative machine-learning methods. 29 …”
Section: Introductionmentioning
confidence: 99%
“…For example, Chang et al found that, compared to support vector machine (SVM), a GNN model of electroencephalography-based brain networks showed better performance in distinguishing among first-episode, chronic schizophrenia patients and controls. 28 Likewise, by using GNN combined with functional connectome data, Oh et al achieved a classification accuracy of 83.13%, which outperformed alternative machine-learning methods. 29 …”
Section: Introductionmentioning
confidence: 99%
“…Şizofreni teşhisi, psikiyatristler tarafından kapsamlı bir şekilde yapılır. Ancak öznel bir bileşeni olan herhangi bir insan temelli karar olarak EEG ve makine öğrenimi yöntemleri hekimlere şizofreni teşhisinde yardımcı olmak için nesnel bir tamamlayıcı olarak görev sağlar [3,22].…”
Section: şIzofreniunclassified
“…Yapılan literatür taraması sonucunda MÖ kullanılarak EEG işareti işleme konuları 18 başlık altında toplanabilir. Bunlar: epilepsi [7,8], duygu durumu [9,10], beyin-bilgisayar arayüzleri [11,12], uyku evreleri [13,14], devinimsel görselleştirme [15,16], zihinsel iş yükü [17,18], Alzheimer [19,20], Sürücü dikkati [1,21], şizofreni [3,22], robotik [23,24], dikkat [2,25], Alkol [26,27], göz kırpmak [4,28], algı [6,29], niyet [30,31], nesnelerin interneti [32,33], kişi kimliği [5,34], beyin hastalığı [35].…”
Section: Introductionunclassified
“…Support vector machine (SVM), which is one of the most commonly used machine learning (ML) methods in pattern recognition ( Lei et al, 2020 ), has been widely utilized as a powerful computational approach to classify schizophrenic patients from healthy controls and predict outcomes based on neuroimaging data ( Wang et al, 2018 ; Chang et al, 2021 ). There are also very few studies that use SVM to classify and predict DS and NDS.…”
Section: Introductionmentioning
confidence: 99%